Visitors' Perceptions of Urban Green Spaces: A Study of Lisbon's Alameda and Estrela Parks - Viebrantz, Petra; Fernandes-Jesus, Maria (Frontiers in Sustainable Cities, 2021)
Urban Green Spaces (UGSs) play a key role in people’s wellbeing, particularly in highly urbanised contexts and possess several elements that may be attractive to visitors. This study focuses on the views and perceptions of visitors of two UGSs located in Lisbon and aimed to determine how they evaluated two different green spaces (Estrela Park and Alameda Park) in terms of physical/natural characteristics, structures, accessibility, surrounding areas, motives for use and importance. Secondly, it sought to explore how people evaluate UGSs in Lisbon in terms of quality and quantity. A total of 188 people responded to a questionnaire composed of close- and open-ended questions. The study revealed that Estrela Park was more valued for its green space characteristics and conservation aspects than accessibility and sports adaptability. Participants visited Estrela Park for its landscape and restful environment and considered the park important to their lives. Although they visited Estrela Park less often, they stayed longer compared to those who visited Alameda Park. Furthermore, regarding the participants’ overall perceptions of the UGSs in Lisbon, many participants mentioned the need for more parks and wanted better preservation and distribution around the city. Most importantly, they valued these spaces and believed that UGS helped them to feel more relaxed and balanced, facilitating socialisation, recreation and physical activities. In conclusion, this study suggests that green and quiet urban parks in Lisbon are valued by the city’s population but they would like to see regular maintenance/cleaning, as well as the provision of leisure activities.